2011
DOI: 10.1111/j.1439-0531.2010.01615.x
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Thyroxine Affects the Morphometric Parameters and VEGF Expression in the Uterus and Placenta and the Uterine Vascularization but does Not Affect Reproductive Parameters in Gilts During Early Gestation

Abstract: The aim of this study was to evaluate the effects of thyroxine administration on morphometric parameters, expression of vascular endothelial growth factor (VEGF) and vascularization in the uterus and placenta and reproductive parameters in gilts at 70 days of gestation. At 150 days of age, i.e., before first heat, 20 gilts were randomly divided into two experimental groups: treated (n=10) and control (n=10). The treated group received a daily dose of 400 μg of L-thyroxine (T(4)) in their diet until slaughter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The changes observed in this study in the placental immunological profile in animals with hypothyroidism and excess of T 4 mirror, at least in part, the fetal-placental changes seen in women and in animals with thyroid dysfunction (Shafrir et al 1994, Morrish et al 1997, Galton et al 2001, Freitas et al 2007, Souza et al 2011, Silva et al 2012. Our study also confirmed the hypothesis of Silva et al (2012) that the migration of trophoblast cells is affected by thyroid dysfunction, particularly in hypothyroidism.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The changes observed in this study in the placental immunological profile in animals with hypothyroidism and excess of T 4 mirror, at least in part, the fetal-placental changes seen in women and in animals with thyroid dysfunction (Shafrir et al 1994, Morrish et al 1997, Galton et al 2001, Freitas et al 2007, Souza et al 2011, Silva et al 2012. Our study also confirmed the hypothesis of Silva et al (2012) that the migration of trophoblast cells is affected by thyroid dysfunction, particularly in hypothyroidism.…”
Section: Discussionmentioning
confidence: 95%
“…However, several of the pathological processes observed in hypothyroidism may result from changes in the placental pro-and anti-inflammatory cytokine profile (Koga et al 2009). In contrast, hyperthyroidism increases reproductive efficiency in experimental animal models (Serakides et al 2001, Freitas et al 2007 and causes significant changes in the uterine vasculature (Souza et al 2011) and in the proliferation of trophoblast cells (Freitas et al 2007). It is important to mention that placental changes similar to those observed in hypo-and hyperthyroidism may also be influenced by the migration kinetics of the trophoblast cells (Knöfler 2010, Hammer 2011, Chakraborty et al 2011, Soares et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…studied the role of thyroid hormones in placentation and found no association. However, there is some evidence that high FT3 and FT4 levels do have a role in vascularization, proliferation and differentiation of the placenta . A recent meta‐analysis on levothyroxine treatment in women with subclinical hypothyroidism undergoing assisted reproductive techniques has indicated that T4‐replacement therapy is beneficial on pregnancy outcomes, possibly indicating a role for thyroid hormones on placentation as well …”
Section: Discussionmentioning
confidence: 99%
“…VEGF and its receptor regulate vascular permeability [ 29 ]. Meanwhile, changes in vascular permeability are involved in the maturation of the endometrium and the implantation window [ 30 , 31 ]. Hosper et al [ 32 ] showed that VEGF presents regular periodic changes on the uterus during the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%